Compare urine albumin to creatinine ration in patients with central and peripheral vertigo - Fattahzadeh-Ardalani, Ghasem; Abbasi, Vahid; Abdolrahimi, Zohreh (International Surgery Journal, 2016)
Background: Vertigo is a symptom of ischemic stroke. In vertigos without neurological symptoms, central vertigo cannot be definitively differentiated from peripheral vertigo. We can use the albumin to creatinine ratio (ACR) of urine in patients with central and peripheral vertigo to differentiate between central and peripheral vertigos which were the aim of this study. Methods: In this descriptive study, 60 patients (30 patients with central and 30 patients with peripheral vertigos) entered study and followed for one year. Necessary documents including age, sex, and medical records were obtained by face to face interview and patient's morning urine samples were sent to the laboratory for analysis of albumin to creatinine ratio. Collected data analyzed by statistical methods in SPSS-19. Results: 65% of patients were female and 35% male. The mean age of patients with central vertigo was 57.2±10.9 and peripheral vertigo was 53±12.5 years. The mean of albumin to creatinine ratio was significantly higher in patients with central vertigo compared to patients with peripheral vertigo (126/53 versus 38/7 mg/g; P=0.001). This difference was significant between men (P = 0.049) and women (P=0.03) of both groups. Also, it was significant in patients with >60 years old compare to others (P=0.002). Conclusions: Results showed that the mean level of albumin to creatinine ratio in patients with central vertigo was significantly higher than patients with peripheral vertigo, it seems that we can use urine albumin to creatinine ratio, as a low-cost test, to differentiate central vertigo from peripheral.